2002
DOI: 10.1557/proc-715-a13.4
|View full text |Cite
|
Sign up to set email alerts
|

Light Induced Defect Creation Kinetics in Thin Film Protocrystalline Silicon Materials and Their Solar Cells

Abstract: Using real time spectroscopic ellipsometry to characterize the microstructure and evolutionary growth of Si:H materials deposited with and without hydrogen dilution, phase diagrams were developed which clearly defined and established growth in the protocrystalline regime. Guided by these phase diagrams thin films and intrinsic layers in p-i-n cell structures were grown which consist solely of the protocrystalline phase so that the bulk uniform properties of the material could be characterized with confidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 24 publications
3
49
0
Order By: Relevance
“…5,[9][10][11][12][13][14][15] Between a-Si: H and c-Si: H-the latter of course already being a class of materials instead of one well-defined material modification-there is an additional form of thinfilm silicon prepared in plasma-enhanced chemical vapor deposition ͑PECVD͒ processes with high hydrogen dilution close to the transition to microcrystalline growth. Such material called polymorph, paracrystalline, protocrystalline, or edge material [16][17][18][19][20] is reported to have reduced defect density, improved stability, and possible medium range order ͑MRO͒. [21][22][23][24][25][26] Such material is since long used as absorber layer in solar cells, in particular, in the top cells of stacked devices.…”
Section: Introductionmentioning
confidence: 99%
“…5,[9][10][11][12][13][14][15] Between a-Si: H and c-Si: H-the latter of course already being a class of materials instead of one well-defined material modification-there is an additional form of thinfilm silicon prepared in plasma-enhanced chemical vapor deposition ͑PECVD͒ processes with high hydrogen dilution close to the transition to microcrystalline growth. Such material called polymorph, paracrystalline, protocrystalline, or edge material [16][17][18][19][20] is reported to have reduced defect density, improved stability, and possible medium range order ͑MRO͒. [21][22][23][24][25][26] Such material is since long used as absorber layer in solar cells, in particular, in the top cells of stacked devices.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been known that crystallites formed in amorphous silicon have different physical profiles depending on the thickness [6]. We look into two identical amorphous silicon thin films but different ones in thickness with the measurements of XTEM, Raman scattering, and XRD.…”
Section: Resultsmentioning
confidence: 99%
“…Several explanations for the increased stability of this type of thin-film silicon -sometimes referred to as protocrystalline, polymorphous, paracrystalline or edge material [7][8][9] -have been proposed. It is reported that these types of material features increased the medium range order in the silicon network, which led to reduced creation of light induced defects [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%